2019
DOI: 10.3390/jcm8071077
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Neural Recruitment for Error-Related Cerebral Activity in Patients with Moderate-To-Severe Obstructive Sleep Apnea

Abstract: (1) Background: Although it is known that obstructive sleep apnea (OSA) impairs action-monitoring function, there is only limited information regarding the associated cerebral substrate underlying this phenomenon. (2) Methods: The modified Flanker task, error-related event-related potentials (ERPs), namely, error-related negativity (ERN) and error positivity (Pe), and functional magnetic resonance imaging (fMRI) were used to evaluate neural activities and the functional connectivity underlying action-monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…48 The ACC has also been shown to participate in central cardiovascular and respiratory control. 49 We observed decreased nodal degree and betweenness in the right ACC in OSAHS patients, which was supported by the results of a fMRI study by Chou et al 50 who found a decreased correlation in multiple ACC functional-connected areas in patients with OSAHS compared with normal subjects. Furthermore, previous structural MRI studies have demonstrated that reduced gray matter volume 16,51 or cortex atrophy 18 occurs in the anterior cingulate gyrus, which may result in decreased nodal degree and betweenness in the ACC in the corresponding structural covariance network.…”
Section: Osahs-related Alterations In Regional Network Parameterssupporting
confidence: 85%
“…48 The ACC has also been shown to participate in central cardiovascular and respiratory control. 49 We observed decreased nodal degree and betweenness in the right ACC in OSAHS patients, which was supported by the results of a fMRI study by Chou et al 50 who found a decreased correlation in multiple ACC functional-connected areas in patients with OSAHS compared with normal subjects. Furthermore, previous structural MRI studies have demonstrated that reduced gray matter volume 16,51 or cortex atrophy 18 occurs in the anterior cingulate gyrus, which may result in decreased nodal degree and betweenness in the ACC in the corresponding structural covariance network.…”
Section: Osahs-related Alterations In Regional Network Parameterssupporting
confidence: 85%
“…Moreover, OSA triggers compensatory or adaptive responses in the brain, such as increased activation or deactivation in specific regions or networks, increased connectivity or plasticity in others, or higher brain volume or metabolism in some areas. These responses reflect an attempt to maintain cognitive function or cope with OSA's adverse effects (Chou et al., 2019 ; Tahmasian et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%